1996
DOI: 10.1159/000237305
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mast Cells, Basophils and Their Mediators in Adverse Reactions to General Anesthetics and Radiocontrast Media

Abstract: General anesthetics and radiocontrast media (RCM) can cause anaphylactic or anaphylactoid reactions. These are usually underdiagnosed and underreported, but their incidence is apparently rising. Their pathogenesis is complex and not completely understood, but the release of vasoactive mediators from basophils and mast cells plays a central role. The recent development of in vitro techniques to study the release of preformed (histamine and tryptase) and de novo synthesized mediators (PGD2, LTC4<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…This statement is based on in vitro studies, which have shown that histamine is released from human basophils in the presence of high concentrations of X-ray CM. There are no in vivo results which indicate that the delayed cutaneous eruptions to nonionic CM are caused by direct release of histamine from skin mast cells [90]. Such a mechanism would be concentration dependent and result in an immediate reaction.…”
Section: Nonspecific Mast Cell Activationmentioning
confidence: 98%
“…This statement is based on in vitro studies, which have shown that histamine is released from human basophils in the presence of high concentrations of X-ray CM. There are no in vivo results which indicate that the delayed cutaneous eruptions to nonionic CM are caused by direct release of histamine from skin mast cells [90]. Such a mechanism would be concentration dependent and result in an immediate reaction.…”
Section: Nonspecific Mast Cell Activationmentioning
confidence: 98%
“…The poor in vitro response of skin mast cells to RCM suggests that these reactions involves complement activation and anaphylatoxin formation that may trigger skin mast cell degranulation in vivo [47,50,60].…”
Section: Radiographic Contrast Mediamentioning
confidence: 99%
“…Studies have demonstrated that hyperosmolarity may be more important in inducing histamine release from basophils than from mast cells as a correlation between histamine release and osmolarity is apparent in basophils but not in mast cells [57,60]. Indeed while agents of low osmolarity Hexabrix and Optipray have been demonstrated to induce concentration dependent histamine release from human lung parenchymal mast cells; Telebrix, a high osmolarity RCM which activates basophils, did not induce histamine release from human lung mast cells [57,60].…”
Section: Radiographic Contrast Mediamentioning
confidence: 99%
See 2 more Smart Citations